DEMOGRAPHIC POLICY AND THE ANALYSIS OF IRRETRIEVABLE LOSSES OF PUBLIC HEALTH BASED ON THE CONCEPT OF THE EPIDEMIOLOGICAL TRANSITION - Григорьев, Юрий Аркадьевич; Баран, Ольга Ивановна (Medicine in Kuzbass, 2017)
From the general positions of population dynamics, the demographic policy is considered, its regional features in the East of Russia are designated. It is necessary to consolidate the positive traditions of the moral and legal norms of the society and the harmonious personality development. It takes their long-term translation for the improvement of the person himself, his family-marriage relations to support the forms of demographic behavior aimed at the expanded population reproduction. The solution of the numerous tasks of the demographic policy presupposes further scientific (theoretical and applied) studies of the features of the socio-demographic and medico-demographic development of the Russian regions. Particular attention should be paid to the analysis of the main characteristics of the epidemiological transition, where mortality, as well as birth rate, is one of the main characteristics of the population reproduction. This will make it possible to define more precisely the prediction of the value of irretrievable losses with endogenous and exogenous determination, to estimate on this basis the reserves of increasing life expectancy through the measures of demographic policy.
Keywords: demographic policy; family-marriage relations; public health; population reproduction; mortality; life expectancy; epidemiological transition